1990
DOI: 10.21273/jashs.115.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Fall Performance and Post-dormancy Growth of `Midiron' Bermudagrass in Response to Nitrogen, Iron, and Benzyladenine

Abstract: Field research was conducted to determine the effects of N, Fe, and benzyladenine (BA) on fall performance, post-dormancy recovery, and storage nonstructural carbohydrate composition of `Midiron' bermudagrass [Cy - nodon dactylon (L.) Pers.]. Fall green color retention and turf quality were superior for 48 than for 24 kg N/ha per month. Nitrogen level did not affect post-dormancy recovery or nonstructural carbohydrate levels in stolons and rhizomes measured in Sept. and Nov. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 15 publications
4
24
1
Order By: Relevance
“…This differs from what was observed in other bermudagrass studies. White and Schmidt () found greater fall colour retention in Midiron bermudagrass that received 4.8 g N m −2 month −1 compared to 2.4 g N m −2 month −1 . Similarly, Gibeault, Richard, and Cockerham () documented an increase in fall colour retention of “Princess 77” bermudagrass when fertilized monthly versus every 2 months with 5 g N m −1 .…”
Section: Resultsmentioning
confidence: 99%
“…This differs from what was observed in other bermudagrass studies. White and Schmidt () found greater fall colour retention in Midiron bermudagrass that received 4.8 g N m −2 month −1 compared to 2.4 g N m −2 month −1 . Similarly, Gibeault, Richard, and Cockerham () documented an increase in fall colour retention of “Princess 77” bermudagrass when fertilized monthly versus every 2 months with 5 g N m −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have stated that the soluble sugar of warm season grasses including zoysiagrass was increased in stolon and rhizomes during fall (Dunn and Nelson ; Rogers et al . ; White and Schmidt ; Fry et al . ; Bush et al .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, many physiological changes were associated with the low temperature acclimation. Some studies have stated that the soluble sugar of warm season grasses including zoysiagrass was increased in stolon and rhizomes during fall (Dunn and Nelson 1974;Rogers et al 1975;White and Schmidt 1990;Fry et al 1993;Bush et al 2000;Ball et al 2002;Shahba et al 2003;Cai et al 2004;Lu et al 2005). Patton et al (2007a) found the concentration of soluble sugars in zoysiagrass increased during cold acclimation and the higher concentrations of total reducing sugars was posi-tively associated with zoysiagrass' freeze tolerance.…”
Section: Seasonal Green Color Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of N fertilizers to turf is known to lower the total non‐structural carbohydrate concentrations in leaf and crown tissues (Hull, 1992). White and Schmidt (1990) used a narrow range of N rates and found no effect on carbohydrate levels in stolons of ‘Midiron’ bermudagrass. Trenholm et al (1998), however, found that N fertilization in Florida decreased TNC levels in two dwarf varieties.…”
Section: Discussionmentioning
confidence: 97%